2010
DOI: 10.2500/aap.2010.31.3351
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine auto-injector use and demographics in a Veterans Administration population

Abstract: The epinephrine auto-injector has been widely used over a long period of time. Certain aspects of this therapy and demographic data, however, have not been well studied. This study investigates patient use and understanding of epinephrine auto-injector use. As part of an ongoing quality assurance program, we evaluated 66 patients who had been given an epinephrine auto-injector and followed in the Allergy and Immunology Clinics at the West Los Angeles Veterans Medical Center. Data analyzed included patient demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…evaluated nearly 15,000 patients in a health maintenance organization (HMO) over a 6‐year period and found that less than 50% refilled their EAI even once and that only 11% refilled consistently at all expected refill times. Several studies performed over the last 15 years have consistently shown that only 50% to 60% of patients carry their EAI with them regularly and can produce them at their office visits …”
Section: Discussionmentioning
confidence: 99%
“…evaluated nearly 15,000 patients in a health maintenance organization (HMO) over a 6‐year period and found that less than 50% refilled their EAI even once and that only 11% refilled consistently at all expected refill times. Several studies performed over the last 15 years have consistently shown that only 50% to 60% of patients carry their EAI with them regularly and can produce them at their office visits …”
Section: Discussionmentioning
confidence: 99%
“…The study of Sirin [3] recommends that training be repeated every 6 months. Several studies have shown that less than 60% of patients carry their EAI with them regularly [19].…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating patient-driven barriers to prompt epinephrine administration during an event, a study of 66 patients who had been prescribed an EAI at an Allergy and Immunology clinic at a VA medical Center revealed that 92% of patients knew how to use their EAI properly but only 58% consistently carried their device. 45 Cost to the patient may also hinder access. In a survey of 917 patients in the US who had been prescribed an EAI, 89% reported filling prescriptions; however, of the ones who did not, 25% cited that cost as the reason.…”
Section: Barriers To Auto Injectable Epinephrinementioning
confidence: 99%